The aryl hydrocarbon receptor in β-cells mediates the effects of TCDD on glucose homeostasis in mice - Myriam P. Hoyeck; Ma. Enrica Angela Ching; Lahari Basu; Kyle van Allen; Jana Palaniyandi; Ineli Perera; Emilia Poleo-Giordani; Antonio A. Hanson; Peyman Ghorbani; Morgan D. Fullerton; Jennifer E. Bruin (Elsevier, 2024)
Objective: Chronic exposure to persistent organic pollutants (POPs) is associated with increased incidence of type 2 diabetes, hyperglycemia, and poor insulin secretion in humans. Dioxins and dioxin-like compounds are a broad class of POPs that exert cellular toxicity through activation of the aryl hydrocarbon receptor (AhR). We previously showed that a single high-dose injection of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD, aka dioxin; 20 μg/kg) in vivo reduced fasted and glucose-stimulated plasma insulin levels for up to 6 weeks in male and female mice. TCDD-exposed male mice were also modestly hypoglycemic and had increased insulin sensitivity, whereas TCDD-exposed females were transiently glucose intolerant. Whether these effects are driven by AhR activation in β-cells requires investigation. Methods: We exposed female and male β-cell specific Ahr knockout (βAhrKO) mice and littermate Ins1-Cre genotype controls (βAhrWT) to a single high dose of 20 μg/kg TCDD and tracked the mice for 6 weeks. Results: Under baseline conditions, deleting AhR from β-cells caused hypoglycemia in female mice, increased insulin secretion ex vivo in female mouse islets, and promoted modest weight gain in male mice. Importantly, high-dose TCDD exposure impaired glucose homeostasis and β-cell function in βAhrWT mice, but these phenotypes were largely abolished in TCDD-exposed βAhrKO mice. Conclusion: Our study demonstrates that AhR signaling in β-cells is important for regulating baseline β-cell function in female mice and energy homeostasis in male mice. We also show that β-cell AhR signaling largely mediates the effects of TCDD on glucose homeostasis in both sexes, suggesting that the effects of TCDD on β-cell function and health are driving metabolic phenotypes in peripheral tissues.